Effects of high altitude on renal physiology and kidney diseases - Wang, Si-Yang; Gao, Jie; Zhao, Jing-Hong (Frontiers in Physiology, 2022)
The hypobaric and hypoxic conditions of high-altitude areas exert adverse effects on the respiratory, circulatory and nervous systems. The kidneys have an abundant blood supply (20%~25% of cardiac output) and high blood flow; thus, they are susceptible to the effects of hypoxia. However, the effects of acute and chronic exposure to high altitudes on renal physiology and pathology are not fully understood. Moreover, few studies have investigated the impact of high-altitude exposure on patients with chronic kidney disease or acute kidney injury. In this review, we summarized changes in renal physiology and renal pathology due to high-altitude exposure as well as the impact of high-altitude exposure on existing kidney diseases, with the aim of informing the prevention and treatment of kidney diseases at high altitudes.